(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Internal audit plays a critical role in ensuring accountability, transparency, and effective governance within public sector organizations. This article explores the key challenges faced by internal audit functions in public sector entities and offers recommendations to enhance their effectiveness. The focus is on strengthening internal control systems, improving auditor independence, and adopting advanced technologies to streamline audit processes.